Melanoma cell–derived exosomes promote epithelial–mesenchymal transition in primary melanocytes through paracrine/autocrine signaling in the tumor microenvironment - Xiao, Deyi; Barry, Samantha; Kmetz, Daniel; Egger, Michael; Pan, Jianmin; Rai, Shesh N.; Qu, Jifu; McMasters, Kelly M.; Hao, Hongying (Cancer letters, 2016)
•Melanoma cell–derived exosomes promote phenotype switching in primary melanocytes.•MAPK pathway and let-7i were involved in exosome-mediated EMT.•EMT-related miRNAs (miR-191and let-7a) in exosomes may be used for melanoma diagnosis.•Targeting exosome-mediated EMT may be an approach to prevent tumor progression. The tumor microenvironment is abundant with exosomes that are secreted by the cancer cells themselves. Exosomes are nanosized, organelle-like membranous structures that are increasingly being recognized as major contributors in the progression of malignant neoplasms. A critical element in melanoma progression is its propensity to metastasize, but little is known about how melanoma cell–derived exosomes modulate the microenvironment to optimize conditions for tumor progression and metastasis. Here, we provide evidence that melanoma cell–derived exosomes promote phenotype switching in primary melanocytes through paracrine/autocrine signaling. We found that the mitogen-activated protein kinase (MAPK) signaling pathway was activated during the exosome-mediated epithelial-to-mesenchymal transition (EMT)-resembling process, which promotes metastasis. Let-7i, an miRNA modulator of EMT, was also involved in this process. We further defined two other miRNA modulators of EMT (miR-191 and let-7a) in serum exosomes for differentiating stage I melanoma patients from non-melanoma subjects. These results provide the first strong molecular evidence that melanoma cell–derived exosomes promote the EMT-resembling process in the tumor microenvironment. Thus, novel strategies targeting EMT and modulating the tumor microenvironment may emerge as important approaches for the treatment of metastatic melanoma.